The Effect of Breastfeeding on Intelligence Quotient and Social Intelligence Among Seven- to Nine-Year-Old Girls: A Pilot Study - AlThuneyyan, Danyah Abdullah; AlGhamdi, Faten Fahad; AlZain, Ragad Nasser; AlDhawyan, Zainab Sami; Alhmly, Haya Fahad; Purayidathil, Tunny Sebastian; AlGindan, Yasmin Yussuf; Abdullah, Ahmed Amr (Frontiers in Nutrition, 2022)
Background: Breastfeeding is an optimal infant feeding method that provides adequate nutrients, achieves healthy growth and development, and enhances the health status of both infants and mothers. Breast milk contains a variety of substances that might positively affect cognition and the development of children’s psychomotor abilities. Objective: This study aimed to examine the variations in intelligence quotient (IQ), social intelligence (SI), and body mass index (BMI) among 7- to 9-year-old girls who were exclusively breastfed, exclusively bottle-fed, or mixed-fed during their first six months of life. Methods: This study involved 111 healthy girls, aged seven to nine years old, who were recruited from nine government and private schools in Dammam, Kingdom of Saudi Arabia. Raven’s Colored Progressive Matrices were used to measure the participants’ IQs, and the Vineland Social Maturity Assessment was used to measure SI through individual interviews. Anthropometric measurements were obtained using standard methods. Results: The breastfed group showed a greater number of above-average IQ test scores (35% vs. 23%; P = 0.479) and better SI scores (78% vs. 55%; P=0.066) compared with the bottle-fed group. The number of girls with normal BMIs was significantly higher in the breastfed group than in the bottle-fed (68% vs. 41%; P=0.045) or mixed-fed groups. Conclusion: Exclusively breastfed girls had higher IQ and SI results compared with bottle-fed girls. However, unlike the BMI differences, these results were not statistically significant. This study provides fundamental observational data and can be further modified for use on a larger national-scale level.